Pembuatan Sistem Administrasi dan Keuangan Berbasis Responsibility Center di Gereja Kebangkitan Kalam Allah Indonesia Jemaat Tenggilis Mejoyo - Budi, Wijaksana; Liliana, Liliana; Setiabudi, Andy (Jurnal Infra, 2016)
Gereja Kebangkitan Kalam Allah Indonesia (GKKA) is a non-profit organization that has been established since 1984. GKKA located on Highway Tenggilis Mejoyo 87 Surabaya has a need for the technology. The current condition of the church experienced problems in the financial and administrative records.This paper will be made an administration and finacial system to help resolve problems that occur in the GKKA. Administration system will help resolve problems in the recording of church members, employees, and assets of the church. The financial system will help in the financial records at each responsibility center. Financial records on the system using the cash basis method. This system is in the form of a website with the programming language PHP and uses a MySQL database.The results to be obtained from applications that have been made, among others, accounting journals, reports, among others: the balance sheet, trial balance, general ledger, reports surplus / deficit.